COMPREHENSIVE STUDY OF CONCEPTUALIZATION OF MODERN VIEWS ON THE DEFINITION OF ECONOMIC SECURITY OF ENTERPRISES: SYSTEM APPROACH - VIVCHAR Vіktor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the conceptual foundations of defining the economic security of commercial enterprises through a systemic and strategic approach. It is emphasized that in the modern business environment, economic security is a key prerequisite for stable development and competitiveness of trade enterprises. The study substantiates that economic security encompasses a set of organizational, economic, legal, financial, informational, and institutional measures aimed at preventing threats, preserving resource potential, and ensuring operational efficiency. The main internal and external risk factors affecting the security of trading structures are identified, including the imperfection of the regulatory environment, instability of financial markets, corruption, low innovation activity, and weak competitiveness. It is emphasized that the system of economic security should have a preventive nature and be based on the principles of complexity, adaptability, and forecasting. The article generalizes various scientific approaches to interpreting the concept of “enterprise economic security” and proposes the author’s definition, which highlights the need for systemic risk management and strategic planning. A conceptual model of the economic security system of commercial enterprises is developed, which includes mechanisms for resource protection, threat diagnostics, risk monitoring, strategic planning, and performance control. The main criteria for assessing the reliability and effectiveness of the system are identified as operational stability, protection of financial and material assets, the ability to counter crisis situations, and ensuring sustainable development. The proposed approach can serve as a methodological basis for developing effective strategies for strengthening the economic security of commercial enterprises under dynamic market conditions.